The mediating role of rumination in the relationship between insomnia and non-suicidal self-injury of college students - Wang, Hanqing; Sun, Hongli (Frontiers in Psychology, 2024)
Introduction: Non-suicidal self-injury (NSSI) is a high-risk factor for suicide, which is widespread among college students and is closely associated with psychological issues. Insomnia tends to cause mental instability, and chronic insomnia can trigger severe mood swings, including anxiety, depression, and irritability. It can also lead to memory loss and metabolic disorders. College students are in a critical period of selfdevelopment, with significant vulnerability to insomnia and NSSI.This study investigated the influence of insomnia on NSSI among college students and examined the significance of rumination as a mediating factor.Methods: Using random cluster sampling, we selected 667 college students from Jiangsu, China, and evaluated them using the Athens Insomnia Scale (AIS), Adolescent Self-Injury Scale (ASIS), and Ruminative Responses Scale (RRS). The significance of the mediating effect of rumination on the relationship between insomnia and NSSI among college students was tested using Bootstrap methods.The fact that the students were only children was statistically significant for rumination scores. (p<0.05). The results showed a significant positive correlation among insomnia, NSSI, and rumination (r=0.198, 0.737, 0.243, respectively; p<0.001).Insomnia of college students affects NSSI directly and indirectly through rumination.Rumination fully mediated the relationship between insomnia and NSSI among college students, indicating an indirect influence of insomnia on NSSI. Total effect value is 0.192. Rumination plays a complete mediating role in the relationship between insomnia and NSSI among college students, with a mediating effect of 84.21%.